Pregnancy with Legg Calve Perthes Disease A Case Report (Bangabandhu Sheikh Mujib Medical University Journal, 2011)
Legg Calve Perthes’ Disease (LCPD) is a hip deformity most common in newborns and children, however it can also affect adults. It is a condition in which the femoral head softens and breaks down. It tends to get better with the age, so in most cases a childhood Perthes’ sufferer will not suffer at all into adulthood apart from the obvious of being significantly short in height for their age. A 25yrs old primigravid lady was admitted at 36+wks pregnancy with Gestational Diabetes Mellitus(GDM) with H/O Bronchial asthma with old Perthes’ Disease. She had pain in left hip which increases on movement. This pain and restricted movement of hip increases as pregnancy advances. Her left lower limb was shortened by 0.5cm.Elective caesarean section was done under spinal anaesthesia. A healthy baby was delivered. Her postoperative period was uneventful. The patient was discharged on 6th postoperative day(POD). Key words: Legg calve Perthes’ Disease; Pregnancy DOI: http://dx.doi.org/10.3329/bsmmuj.v4i2.8645 BSMMU J 2011; 4(2):125-127